Important Anatomy in Lymphatic Interventions: A Practical Review - Crawford, Daniel A.; Patel, Indravadan J.; Naidu, Sailendra G.; Wallace, Alex; Ozen, Merve; Alzubaidi, Sadeer (Seminars in Interventional Radiology, 2025)
New understanding of the lymphatic system as well as increasing recognition of its importance in various pathologies have increased the opportunity to perform lymphatic interventions. Advancement in our understanding of the lymphatic system anatomy, including variations, combined with improved imaging has renewed interest in both surgical and interventional management of a wide range of complex lymphatic pathologies. It is important for the proceduralist to recognize the anatomy, variability, and physiology of the lymphatic system, including lower extremity lymphatic drainage, cisterna chyli location, and thoracic duct drainage. The purpose of this study is to convey the practical aspects of performing lymphatic interventions in an effort to improve the speed and reliability of these procedures.
Keywords: anatomy; lymphatic; interventional radiology; embolization; development